REPRESENTASI PEREMPUAN DALAM PEMILIHAN UMUM 2019 DI KOTA BEKASI - Nurul Sumarheni (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2022)
The representation of women in politics is a must in a democratic country. Since it was rolled out through several electoral regulations after the Reformation, Affirmative action quota of 30% for women, has not yet reached the expected target. Although at the nomination stage, 30% of women were required to be represented, in the end the candidates who were elected had never reached 30%. Nationally, the highest is only 20.5%. In Bekasi City, the same thing happened. Of the 50 seats in the Bekasi City DPRD, only 8 seats were successfully occupied by women. That is, only 16% of the total number of seats. This low income is influenced by many factors. First, the internal factor of political parties. For example, ideology, the lack of female members occupying strategic positions and the lack of party collective awareness to prioritize increasing the quantity and quality of female cadres; second, external factors. Among other things, regulations that do not explicitly guarantee women's representation; the open proportional system makes the affirmative action policy paralyzed. In addition, there is still a high level of patriarchal culture in society